2017
DOI: 10.1161/str.48.suppl_1.wp381
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP381: The Culture Influence on Coping and Adaptation to Stroke Caregiving: the Chinese Family Caregivers’ Experience

Abstract: Introduction: In China, the estimated number of stroke survivors is 22.5 million, of which 78% need home care. It has been indicated that culture could play a major role on the stroke caregiving experiences. Understanding stroke caregivers’ coping and adaptation within Chinese culture is needed. Objective: To explore how Chinese culture influences the coping and adaptation to stroke caregiving among stroke caregivers. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This belief system suggests people accept the reality of caregiving (Yen et al, 2009). Qiu et al (2017) found some Chinese family caregivers used fatalistic appraisal which is an emotional coping strategy that involves “Ming” (fate) to help them adapt the caregiving reality. The belief “Ming” means “following the nature of universe and the principles of how things work” (S. W. C. Chan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This belief system suggests people accept the reality of caregiving (Yen et al, 2009). Qiu et al (2017) found some Chinese family caregivers used fatalistic appraisal which is an emotional coping strategy that involves “Ming” (fate) to help them adapt the caregiving reality. The belief “Ming” means “following the nature of universe and the principles of how things work” (S. W. C. Chan, 2010).…”
Section: Discussionmentioning
confidence: 99%